Efektivitas Program Kampung Keluarga Berkualitas dalam Meningkatkan Kesejahteraan Keluarga di Desa Ciherang Kecamatan Banjarsari Kabupaten Ciamis - Ilham Mawardi; Irfan Nursetiawan; Fachmi Syam Arifin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by problems in the Effectiveness of the Quality Family Village Program in Improving Family Welfare in Ciherang Village, Banjarsari District, Ciamis Regency, including: 1) Challenges in improving family welfare through the Quality Family Village Program, 2) The lack of structured and sustainable family group development, 3) Demands for increasing the effectiveness of mechanisms in coaching, socialization and counseling for family welfare in Ciherang Village, 4) The need for educational strategies for Family Groups targeted by the program. The purpose of this study is to determine the effectiveness of the Quality Family Village Program in Ciherang Village. The method used in this study is a descriptive analysis method with a qualitative research approach. This study uses primary and secondary data sources. The primary data from this study are the results of interviews with several predetermined informants consisting of Ciherang Village government officials, Program management/implementation coordinators, related groups/communities. Secondary data in this study are documents that are relevant to the research. Data collection techniques in this study consist of observation, interviews, and documentation. The data analysis process in this study includes data reduction, data classification, data analysis, and conclusion drawing.